وأثره على سيكولوجية الطفل من منظور الاسرة الجزائرية Covid-19 الحجر الصحي المنزلي كإجراء وقائي ضد - جاب الله, حسين; بن عبد الرحمان, سيد علي (جامعة الوادي - University of Eloued, 2020)
يعيش العالم اليوم في وضع مخالف للعادة وهذا نتيجة لظهور فيروس يعرف ب "كوفيد-19" حيث انتهجت معظم الدول تدابير من شأنها الحد من الانتشار السريع له وكان الحجر الصحي المنزلي كأحد هاته التدابير الوقائية، وعمدنا في دراستنا هذه إلى معرفة اثر هذا الأخير على سيكولوجية الطفل من منظور الأسرة الجزائرية، ومن بين النتائج التي توصلنا إليها هي أن سيكولوجية الطفل قد تأثرت بهذا الإجراء فهو يراه أمرا مخالفا لعادته ويحد من حريته، وكحلول مقترحة من الضروري على الأسر التفكير في أشياء قد تجعل الطفل في راحة وطمأنينة داخل المنزل مع ضمان احترام قواعد وتدابير الوقاية، من خلال التوعية الدائمة والمستمرة للأطفال بلغة بسيطة حسب مستوى فهممهم واستيعابهم حول هاته الإجراءات وأسلوب الحياة المعتمد في هاته الفترة، وتحسيسهم أن هذا الإجراء مؤقت وفيه مصلحة للجميع وأن الالتزام بتطبيقه يقلل من خطورة هذا المرض ويعجل بسرعة العودة إلى الحياة الطبيعية.The study aimed to know the effect of the Corona pandemic on the level of health awareness among students, as we followed this in our research on the descriptive method and we did the questionnaire and the questionnaire was the main method used in collecting data, and the research community was represented in the students of the University of Tebessa, which was studied using a random sample method, and after delving into the processes The study found that there is a positive impact of the Covid-19 pandemic on the level of students' health awareness, in addition to the effect of the general behavior of the student and his behavior in the living environment in which he lives at the present time. As suggested solutions, we see that adopting a social distancing policy and applying preventive measures and the gradual return of various life activities is imperative. One of them, considering this experience as previous experiences increases the importance of a person's awareness of preserving his health and his sense of responsibility for everything that happens around him
The impact of the Covid-19 pandemic on the level of health awareness among students
مقال
Keywords: الحجر الصحي ، سيكولوجية الطفل ، الاسرة; Covid-19, Health Awereness, Student, University.